Shallow subsurface structure estimated from dense aftershock records and microtremor observations in Furukawa district, Miyagi, Japan. Issue 1 (1st March 2017) - Goto, Hiroyuki; Mitsunaga, Hitoshi; Inatani, Masayuki; Iiyama, Kahori; Hada, Koji; Ikeda, Takaaki; Takaya, Toshiyasu; Kimura, Sayaka; Akiyama, Ryohei; Sawada, Sumio; Morikawa, Hitoshi
Abstract : We conducted single-site and array observations of microtremors in order to revise the shallow subsurface structure of the Furukawa district, Miyagi, Japan, where severe residential damage was reported during the Great Eastern Japan Earthquake of 2011, off the Pacific coast of Tohoku. The phase velocities of Rayleigh waves are estimated from array observations at three sites, and S-wave velocity models are established. The spatial distribution of predominant periods is estimated for the surface layer, on the basis of the spectral ratio of horizontal and vertical components (H/V) of microtremors obtained from single-site observations. We then compared ground motion records from a dense seismometer network with results of microtremor observations, and revised a model of the shallow ( 100 m) subsurface structure in the Furukawa district. The model implies that slower near-surface S-wave velocity and deeper basement are to be found in the southern and eastern areas. It was found that the damage in residential structures was concentrated in an area where the average value for the transfer functions in the frequency range of 2 to 4 Hz was large. Abstract : Severe residential damage in the Furukawa district, Miyagi, Japan, occurred during the Great Eastern Japan Earthquake of 2011. We model the shallow subsurface structure based on aftershock records from a dense seismometer network and results of microtremor observations. Site amplifications estimated from the model explain the damage distribution well.